Stowaway! adventures at sea - West, Tracey, 1965- (New York : Grosset & Dunlap, 2008)
Asks the reader to chose the path of the plot in a story in which the narrator takes an adventure aboard Rockhopper's ship, the "Migrator."
"Pick your path 1."
2.9
3-6
3-6
Keywords: Ships -- Juvenile fiction; Plot-your-own stories; Ships -- Fiction; Plot-your-own stories; Ships -- Fiction; Plot-your-own stories